MISOPROSTOL INDUCTION OF LABOR IN PREGNANCY POSTTERM - Lindo, M. (2015)
OBJETIVE:To determine characteristics and complications of labor induction with intravaginal misoprostol (50 mcg) in post?date pregnancy (gestacional age > 41 weeks) with unfavorable cervix (Bishop score £ 6). DESIGN: Retrospective and descriptive study. SETTING: Uldarico Rocca Fernandez Hospital, EsSalud, Obstetrical Service, from January to December 2001. MATERIAL AND METHODS: A total of 104 patients with post?date pregnancy, with a reactive non?stress test and negative stress test, and who had undergone labor induction with intravaginal misoprostol 50 mcg administered every 6 hours to obtain appropriate uterine dynamics or a total of 200 mcg were studied. RESULTS: Labor induction was followed by vaginal delivery in 87 (83,7%) patients, 67 (77%) before 24 hours. Interval from begining of induction to delivery was significantly shorter in multiparae (11,5+7,1 hours) than nulligravida (17,1 ± 11,4 hours); 74 (85%) used only 2 misoprostol doses. The cesarean rate was 16,3% (17 cases) and the main cause was failed induction in 11 cases (64,7%). There were 4 cases of tachysystole (3,6%) and 2 cases of hypertonus (2,9%). All neonates had Apgar score > 7 at 5 minutes. CONCLUSIONS: The use of 50 mcg intravaginal misoprostol is an effective alternative for labor induction in post?date pregnancy, it did not increase cesarean rates but require strict cardiofetal monitoring during induction.